Les messages portés par les produits agroalimentaires positionnés sur la santé. Intentions des émetteurs ou émettrices et réception dans les familles - Mélanie Porte (Communiquer)
In a context of medicalization of food and of accountability of industrialists and consumers for the alleged harms of certain food practices on health, this article constitutes a proposal for formalizing the differences between, on the one hand, the expectations of an agri-food company putting messages on its products that imply a more health-friendly composition, and on the other hand, the forms of appropriation that are made of them in families. Articulating approaches to socio-anthropology of food (Poulain, 2002) and Actor-Network Theory (Callon I., 2006), we categorize and describe these differences based on interviews and observations conducted between 2018 and 2019, in companies, supermarkets, and families' homes. These shifts, which are more or less significant, reflect the space of freedom that families have within a system in which agri-food companies send messages about the norms of “eating well”.